Effect of axitinib regulating the pathological blood–brain barrier functional recovery for glioblastoma therapeutics. (29th December 2021) - Zhang, Fengtian; Wen, Lijuan; Wang, Kai; Huang, Zhihua; Jin, Xiangyu; Xiong, Ruiwen; He, Shiying; Hu, Fuqiang
Abstract: Aims: Dysfunction of the blood–brain barrier (BBB) is a prominent pathological feature of glioblastoma (GBM). Vascular endothelial growth factor (VEGF) is confirmed to be abnormally elevated in the pathogenesis of GBM, causing BBB pathological disruption, which further allows the leakage of neurotoxic blood‐derived molecules into the central nervous system (CNS), interfering brain homeostasis and leading to poor patient outcome. Since BBB is an integral and pivotal part of the brain microenvironment, which strongly supports the occurrence and the pathological progression of GBM, here we have selected the VEGFR antagonist axitinib as a BBB functional regulator and hypothesized to regulate pathological BBB restoration for GBM effective treatment. Methods: The pathological BBB cell model was constructed to investigate the timeliness and dose effect of axitinib regulating pathological BBB restoration. In order to investigate the efficacy and safety of axitinib regulating pathological BBB restoration for anti‐GBM treatment, the orthotropic GBM‐bearing mice model was established for in vivo study, and bioluminescent imaging was used to real‐time and noninvasively monitor tumor growth response in vivo, and survival time was also recorded. Results: Axitinib under non‐cytotoxic dosage regulated pathological BBB restoration in a time‐dependent mode, and multiple intervention of axitinib could realize a visible restoration of pathological BBB in vitro. Moreover, axitinib treatment restored pathological BBB in orthotropic GBM‐bearing mice. We further confirmed that functional restoration of pathological BBB with axitinib had certain curative effect in prolonging median survival of orthotropic GBM‐bearing mice at non‐cytotoxic dosages in vivo. Conclusion: The mechanism of axitinib involved in BBB functional regulation in the treatment of GBM is first illuminated in this report; moreover, this is the first report first referring to regulating pathological BBB functional recovery for GBM effective therapeutics. Overall, the view of regulating pathological BBB functional recovery may offer a novel sight for other CNS diseases relating to BBB permeability effective therapeutics. Abstract : The occurrence of glioblastoma (GBM) induces blood brain barrier (BBB) pathological damage, and the restoration of pathological BBB induced by axitinib could produce considerable anti‐GBM effect.